Global perception towards GM oil palm: a review / Isnorita Abdullah and Hamizah Othman - Abdullah, Isnorita; Othman, Hamizah (Faculty of Plantation and Agrotechnology, 2018)
The growing of GM technology has arisen the awareness among people in the world. The existence of this biotechnology has. created a lot of consumers attitudes around the world. The objective of this review is to get a clear view about trend changing in consumer attitudes and their perception towards GM oil palm globally. The biotechnology uses gene manipulation by altering organisms DNA to create new traits to crops like generating high production of crops, herbicide tolerance and insect resistance. However, the presence of GM technology was not being welcoming in certain countries like Europe and Japan because of these countries had perception on GM products are harmful and can affect human health and give bad consequences to environment. Unlike China, the government really supportive in encourage the researchers to do further stud) on biotechnology in order to sustain food availability to their people. Malaysia is one of the countries in step of implementing GM technology in certain crops like papaya, rubber and oil palm. Implementing GM technology to palm oil can improve the quality' of palm oil by providing less saturated fats content and GM oil palm surely can generate high production of oil to be supplied to world’s need and support human balanced diet as world population increases for about 7 billion, other vegetable soils like soybean, rapeseed, canola and sunflower cannot be sufficient as they average yield cannot surpass palm oil yield. By the consumers' attitudes towards GM products, GM oil palm surely can be accepted by people globally.